In‐Situ Observation of Storm‐Induced Wave‐Supported Fluid Mud Occurrence in the Subaqueous Yellow River Delta. Issue 7 (6th July 2022) - Liu, Xiaolei; Lu, Yang; Yu, Heyu; Ma, Lukuan; Li, Xingyu; Li, Weijia; Zhang, Hong; Bian, Changwei
Abstract: Two relatively comprehensive and long‐term observation campaigns of bottom sediment dynamics have been conducted at the subaqueous Yellow River delta in the winters of 2016 and 2018. High suspended sediment concentration (SSC) up to 10 g/L were observed in 2016 and active events of wave‐supported fluid mud (WSFM) were found to exist at the abandoned river delta during storms in 2018. A set of calibrated optical backscatter sensors measured the near‐bed SSC >30 g/L with a maximum WSFM thickness >60 cm. WSFMs emerging at the abandoned river delta were classified into three types: single‐peak, multi‐peak, and hybrid according to the time‐varying characteristics of WSFMs. The dominant factors triggering the WSFM generation and dissipation are storm‐wave actions and tidal effects, with limited contribution from current‐induced turbulence. In this study, several lines of evidence were put forward to prove the presence of seabed liquefaction to a depth of 10–16 cm, and thus we can infer that another significant factor enhancing the WSFM thickness scale may be wave‐induced liquefaction. Observations showed obvious signs of WSFM motion, or in other words, wave‐supported gravity flow (WSGF) moved downslope. The downslope velocity (around 1.9 cm/s) was estimated by solving a buoyancy‐friction force balance. This study observed frequent WSFM events at the abandoned Yellow River delta for the first time and demonstrates the need to attach more concerns about its roles in sediment transport and offshore engineering in the future. Plain Language Summary: In estuarine and coastal regions, fluid mud is characterized by a high concentration of suspended sediment (>10 g/L). Supported by wave motions, it can move downslope across the continental shelf. In this study, we conducted comprehensive observations to investigate the fluid mud occurrence in the subaqueous Yellow River delta. We found that fluid mud formed on a silty seabed during winter storms, and it further moved downslope with a relatively small velocity due to gravitational effect. These fluid mud processes were closely related to the sediment liquefaction under storm waves. Key Points: Wave‐supported fluid mud and gravity flow generated during storm events in an abandoned delta with a predominately silty seabed Three types of wave supported fluid mud, including single‐peak, multi‐peak, and hybrid, were found Wave‐induced seabed liquefaction may play an important role in wave‐supported fluid mud formation